Comparative Research Between Sportsman's Heart and Hypertrophic Cardiomyopathy - Abdelbaki, Mourad; Boureghda, A.; Hanifi, N (International Journal of Innovative Research in Medical Science, 2024)
Physiological left ventricular hypertrophy is the result of the left ventricle having to function harder due to intense physical exercise. After exercise is stopped, this modest and reversible hypertrophy persists. Studying these structural alterations is now feasible because to cardiac echodoppler. Distinguishing this adaptive hypertrophy from the pathogenic hypertrophic cardiomyopathy might be challenging at times. We examined 212 athletes who competed and a group of hypertrophic cardiomyopathy patients who had asymmetric septal hypertrophy that was confirmed. The findings demonstrated that there is a boundary between pathological and normal hypertrophy. This zone contained four athletes, one of whom had hypertrophic cardiomyopathy. Numerous variables led to the diagnosis, including the patient's history, electrical anomalies, septal thickness, and a diastolic diameter of less than 45 mm. Deconditioning further supported the diagnosis.